Gastric Cancer in the Countryside or in the City: Does the Prognosis Change? An Analysis from the German States of Brandenburg and Berlin - Andreas Loew; Anne von Ruesten; Constanze Schneider; René Mantke; Karsten H. Weylandt; Stephan Gretschel (Current Oncology)
Background: Medical care structures differ between urban and rural areas. Clinical cancer registries can depict real-world care through detailed data analysis, identifying potential regional disparities and contributing to improvements in healthcare. Methods: Data from the Brandenburg–Berlin Clinical-Epidemiological Cancer Registry for the years of diagnosis 2017–2022 were analyzed to assess the epidemiology and real-world care of gastric cancer, including cardia. Brandenburg was compared to Berlin regarding perioperative treatment regimens. The resulting survival benefits were assessed using Kaplan–Meier and Cox regression models. Results: For the years of diagnosis 2017 to 2022, 5805 cases of gastric carcinoma were documented in the cancer registry. Survival data showed no significant differences between Berlin and Brandenburg. Preoperative therapy for cT3/cT4N0 tumors was significantly more common in Berlin (72%) than in Brandenburg (68%). Perioperative therapy was associated with a survival benefit for stages T3-/T4N+ but not for stages T1N+ or T2. The lower proportion of pre-treated T3/T4N+ patients in rural Brandenburg did not result in a significant survival difference. Conclusions: The data provide a comprehensive representation of the current state of gastric cancer care in these two regions. Gastric cancer treatment outcomes, in terms of survival, are comparable between the rural region of Brandenburg and the urban center of Berlin.